PENINGKATAN MINAT DAN KEMAMPUAN MENULIS CERITA PENDEK MELALUI PENERAPAN MEDIA EMPAT KOTAK BERORIENTASI PENDEKATAN PARTISIPATIF PADA SISWA KELAS IX A SMP NEGERI 1 MANOKWARI - Titaley, Oktofina (JURNAL TRITON PENDIDIKAN, 2016)
Learning and teaching process is not only determined by the teacherâs ability, but also approach, media, and right methods which can be applied in accordance with the contex, presenting the real world into the class and encouraging the students to relate knowledge and its application in daily life.The research Â aims at discussingÂ  how to write short stories through the application of four-box media with participatory approach oriented. Studentsâ involment in the learning and teaching process is expected more dominant, creative and gratifying. Thus, the situation will evolve studentsâ imagination, emotion and sensivity to appreciate. The lesson includes: âupgrading studentsâ interest in writing short stories, âupgrading studentsâ ability to detemine the main ideas based on the steps, upgrading the ability to develop the main ideas to form a short story, upgrading the ability to detemine the title, and uprading the ability to edit friendsâ short story.The subjects of the research are fourty students of Class IX SMP Negeri 1 Manokwari. The results show that writing short stories through four-box media with participatory approach oriented can increase the interest and ability in writing short stories on students of class IX SMP Negeri 1 Manokwari.